Horticulture, Environment, and Biotechnology - Lee, Gung Pyo.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Korean Society for Horticultural Science, co-published with Springer.)
Horticulture, Environment, and Biotechnology (HEB) is the official journal of the Korean Society for Horticultural Science, was launched in 1965 as the "Journal of Korean Society for Horticultural Science". HEB is an international journal, published in English, bimonthly on the last day of even number months, and indexed in Biosys Preview, SCIE, and CABI. The journal is devoted for the publication of original research papers and review articles related to vegetables, fruits, ornamental and herbal plants, and covers all aspects of physiology, molecular biology, biotechnology, protected cultivation, postharvest technology, and research in plants related to environment.
Keywords: Life sciences; Agriculture; Plant ecology; Plant breeding; Life Sciences, general; Plant Breeding/Biotechnology.; Plant Physiology; Agriculture; Plant Ecology